Occupational burnout among healthcare professionals in Obstetrics and Gynecology department of a public hospital in Islamabad, Pakistan / Sabin Kashif - Sabin, Kashif (2020)
The general purpose of this study was to investigate the extent of burnout experienced by healthcare professionals working in obstetrics & gynaecology units in public hospital of Islamabad, Pakistan. Specifically, this research attempted to explore the contributing factors of burnout, by correlating the burnout scores of exhaustion and disengagement, with the sociodemographic variables. The main objectives of the study were: (i) to assess the levels of burnout as determined by the extent of exhaustion and disengagement among the study participants, and (ii) to compare the mean scores of exhaustion and disengagement among healthcare professionals based on different demographic characteristics: (a) age, (b) gender, (c) marital status, (d) level of education, (e) work experience, (f) working hours, and (g) salary of the participants. This study used a cross-sectional, survey research design for data collection. Demographic information, data on disengagement, and exhaustion were collected via a 25 items online survey. Oldenburg Burnout Inventory OLBI was used as the study instrument. OLBI consisted of 16 items, 8 items each for exhaustion and disengagement subscales. Responses were recorded on a four-point Likert scale. Data were analysed by using IBM Statistical Packages for the Social Sciences, IBM SPSS version 26 software package. Response rate of the survey was 71.83%, as 102 of the total 142 eligible health professionals responded to the survey. Ten (9.8%) participants were more than 50 years old, 29 (34.3%) 40-49 years, 28 (27.5%) 30-39 years, and 35 (34.3%) participants aged 20-29 years. Majority of the respondents were female (96.1%). Sixty-seven (65.7%) were iv married. The study sample of 102 consisted of 55 doctors, 43 nurses and 4 operation theatre technicians. Results of the study reported five interesting findings. First, there were high mean exhaustion and disengagement levels: 2.53+0.54 and 2.14+0.57, respectively, indicating that on an average, the study participants experienced above threshold levels of burnout. Approximately 40% of the participants were burned out (experiencing both exhaustion and disengagement), while around 15% did not show burnout at all (both exhaustion and disengagement below threshold levels). Second finding was that above 80% of the participants were exhausted, whereas disengagement was present in 44%. Third, that majority of the participants were females (96.1%). Fourth, that the participants more than 50 years old, were significantly more exhausted and more disengaged as compared to the younger participants. Fifth finding was that healthcare workers working more than 60 hours per week were significantly more exhausted and more disengaged than those working fewer hours than them. This research concluded that there are considerably high burnout levels among obstetrics and gynaecology healthcare professionals in Pakistan. This needs further in-depth investigation and possible interventions to avoid serious consequences and provide better human services. There is a need for workplace rules and policies regarding optimum acceptable working hours, favourable work environments, appropriate work-life balance, and well-designed wellness programs for all healthcare workers, especially for those working in obstetrics and gynaecology. Appropriate measures on individual, departmental, organizational, and government levels are required to address this problem.